Sustainability analysis of selected banner ecotourism development projects in Mindanao, Philippines - Salik, Aleja Plaza (USM R & D Journal, 2010)
The main objective of the study was to analyze the sustainability of selected banner ecotourism development projects in Mindanao. A total of 1,280 eco-tourism stakeholders served as respondents of the study. Eight were administrators/managers; 72 LGU officials; 160 tourists/guests both local and foreign; and 800 community residents. The measurements used in the analyses were descriptive and stepwise regression. Sets of survey questionnaires were employed in gathering the data and vital information. Almost all the banner ecotourism projects in Mindanao are located outside the city but are accessible by all means of transportation. They have operated for five or more years with income levels of P 1 million and above, with operational expense of P 1 million or more per year. Many of them are protected landscapes and national parks with provisions of food and accommodation. Majority of the respondents were married; females; with age that ranged from 30-40; and finished college level of education. Majority of the tourists were Europeans. All ecotourism projects in Mindanao are also highly adequate in terms of project support services from the Philippine government. Further findings showed that almost all ecotourism project had very high sustainability results while in stepwise regression analysis, the location of the project; the type of business; the nationality of the guests; promotions, marketing and infrastructure support of the government; income level of the community residents; and educational qualifications of the projects administrators and managers were the only variables which significantly influenced the sustainability of the selected banner ecotourism projects in Mindanao.